Designing a Virtual-Reality-Based, Gamelike Math Learning Environment. Issue 1 (2nd January 2016) - Xu, Xinhao; Ke, Fengfeng
ABSTRACT: This exploratory study examined the design issues related to a virtual-reality-based, gamelike learning environment (VRGLE) developed via OpenSimulator, an open-source virtual reality server. The researchers collected qualitative data to examine the VRGLE's usability, playability, and content integration for math learning. They found it important to design an intuitive game-control and interaction interface, plot playability via the combination of enjoyable virtual reality features and the rewarding mechanism, create intrinsic and balanced content-gameplay integration, and adapt to different gameplay styles. Participants found the VRGLE engaging and instructive in teaching fractions.